Business Development Strategy: Organic Vegetable Products In Jambon Gesikan Village, Magelang City - Fadli Akbar Lubis; Fatkhiyah Rohmah; Dewi Syahra Anjani; Desti Dwi Hapsari (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2025)
This research aims to develop a strategy for the growth of organic vegetable businesses in Kampung Jambon Gesikan, Magelang City. The research method employed is a survey, collecting primary data through respondents from community representatives and the Environmental Agency of Magelang City, alongside secondary data from relevant literature. Data analysis uses internal and external factor analysis, followed by a SWOT analysis to formulate the development strategy. The findings show that the organic vegetable business in Jambon Gesikan Village is positioned in Quadrant 1 (Aggressive), indicating a strong potential to capitalize on market opportunities. The recommended strategy is an SO strategy, utilizing strengths to seize existing opportunities, including developing vegetable variety diversity, improving organic vegetable product quality, processing products into other derivative goods, and forming marketing partnerships.